Long non-coding RNAs modulate tumor microenvironment to promote metastasis: novel avenue for therapeutic intervention - Baba, Sana Khurshid; Baba, Sadaf Khursheed; Mir, Rashid; Elfaki, Imadeldin; Algehainy, Naseh; Ullah, Mohammad Fahad; Barnawi, Jameel; Altemani, Faisal H.; Alanazi, Mohammad; Mustafa, Syed Khalid; Masoodi, Tariq; Akil, Ammira S. Alshabeeb; et al. (Frontiers in Cell and Developmental Biology, 2023)
Cancer is a devastating disease and the primary cause of morbidity and mortality worldwide, with cancer metastasis responsible for 90% of cancer-related deaths. Cancer metastasis is a multistep process characterized by spreading cancer cells from the primary tumor and acquiring molecular & phenotypic changes, enabling them to expand and colonize in distant organs. Despite recent advancements, the underlying molecular mechanism(s) of cancer metastasis is limited and needs further exploration. In addition to genetic alterations, epigenetic changes have been demonstrated to play an important role in the development of cancer metastasis. Long non-coding RNAs (lncRNAs) are considered one of the most critical epigenetic regulators. By regulating signaling pathways and acting as decoys, guides, and scaffolds, they modulate key molecules in every step of cancer metastasis, including dissemination of carcinoma cells, intravascular transit, and metastatic colonization. Gaining good knowledge of the detailed molecular basis underlying lncRNA-regulating cancer metastasis may provide previously unknown therapeutic and diagnostic lncRNAs for patients with metastatic disease. In this review, we concentrate on the molecular mechanisms underlying lncRNAs in the regulation of cancer metastasis, cross-talk with metabolic reprogramming, modulating cancer cell anoikis resistance, influencing metastatic microenvironment, and interaction with pre-metastatic niche formation. In addition, we also discussed the clinical utility and therapeutic potential of lncRNAs for cancer treatment. Finally, we also represented areas for future research in this rapidly developing field.